Filling the gaps in the research about second primary malignancies after bladder cancer: Focus on race and histology - Othmane, Belaydi; Yi, Zhenglin; Zhang, Chunyu; Chen, Jinbo; Zu, Xiongbing; Fan, Benyi (Frontiers in Public Health, 2022)
Purpose: Previous research has shown that bladder cancer has one of the highest incidences of developing a second primary malignancy. So we designed this study to further examine this risk in light of race and histology. Patients and Methods: Using the SEER 18 registry, we retrospectively screened patients who had been diagnosed with bladder cancer between 2000 and 2018. We then tracked these survivors until a second primary cancer diagnosis, the conclusion of the trial, or their deaths. In addition to doing a competing risk analysis, we derived standardized incidence ratios (SIRs) and incidence rate ratios (IRRs) for SPMs by race and histology. Results: A total of 162,335 patients with bladder cancer were included, and during follow-ups, a second primary cancer diagnosis was made in 31,746 of these patients. When the data was stratified by race, SIRs and IRRs for SPMs showed a significant difference: Asian/Pacific Islanders (APIs) had a more pronounced increase in SPMs (SIR: 2.15; p 0.05) than White and Black individuals who had SIRs of 1.69 and 1.94, respectively; p 0.05. In terms of histology, the epithelial type was associated with an increase in SPMs across all three races, but more so in APIs (IRR: 3.51; 95% CI: 2.11- 5.85; p0.001). Conclusion: We found that race had an impact on both the type and risk of SPMs.Additionally, the likelihood of an SPM increases with the length of time between the two malignancies and the stage of the index malignancy.